Communication Elderly-Children and Elderly-Children in Law, Social Support and Successful Aging in Elderly Men and Women - Endang Nursolehah; Diah Krisnatuti (Journal of Family Sciences, 2017)
The success of elderly life is characterized by the comforting conditions of loving care and attention from family and relatives, health and happy. This study aimed of this research are to determined the different, correlation and effect of communication with children and children in law and social support to success of life on elderly men and women. This research sample are choosen purposively as many as 60 young elderly aged 60-69 years old which is divided into 30 elderly men and 30 elderly women who still have a partner, children and children in law. The largest proportion of elderly on variabel communication elderly-children, communication elderly-children in law, social support and successful in elderly is in the medium category. Communication elderly-children and communication elderly-children in law has a significant positive correlation with social support. Social support is related and has a significant positive effect on the success of elderly life ,it mean that the higher social support will increase the success of elderly life